2003
DOI: 10.1021/ac026239a
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Coupling of Isoelectric Focusing and Free Solution Electrophoresis for Multidimensional Separations

Abstract: We have developed an acrylic microfluidic device that sequentially couples liquid-phase isoelectric focusing (IEF) and free solution capillary electrophoresis (CE). Rapid separation (<1 min) and preconcentration (73x) of species were achieved in the initial IEF dimension. Using full-field fluorescence imaging, we observed nondispersive mobilization velocities on the order of 20 microm/s during characterization of the IEF step. This transport behavior allowed controlled electrokinetic mobilization of focused sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
188
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(191 citation statements)
references
References 37 publications
(64 reference statements)
2
188
0
Order By: Relevance
“…We perform the experiments in an electrokinetic focusing flow configuration which is similar to the primary step of a pinched flow electrokinetic injection (or a three-inlet-channel mixing scheme), where the centre sample stream and sheath flows have mismatched ionic conductivities. As mentioned above, these conditions are relevant to on-chip electrokinetic practices with conductivity gradients such as sample injection for field-amplified sample stacking (see Ren & Li 2004;Bharadwaj & Santiago 2005), flow control and separations of streams with indeterminate sample chemistry, low-Reynolds-number micromixing (see Oddy et al 2001), and flow at the intersection of multidimensional assays using heterogeneous buffer streams (see Herr et al 2003). We explore variations of applied electric field and centre-to-sheath conductivity ratios that impose variations of the electric Rayleigh number across four orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…We perform the experiments in an electrokinetic focusing flow configuration which is similar to the primary step of a pinched flow electrokinetic injection (or a three-inlet-channel mixing scheme), where the centre sample stream and sheath flows have mismatched ionic conductivities. As mentioned above, these conditions are relevant to on-chip electrokinetic practices with conductivity gradients such as sample injection for field-amplified sample stacking (see Ren & Li 2004;Bharadwaj & Santiago 2005), flow control and separations of streams with indeterminate sample chemistry, low-Reynolds-number micromixing (see Oddy et al 2001), and flow at the intersection of multidimensional assays using heterogeneous buffer streams (see Herr et al 2003). We explore variations of applied electric field and centre-to-sheath conductivity ratios that impose variations of the electric Rayleigh number across four orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al [8] discussed their use of methylcellulose to reduce electroosmosis and peak drift for IEF in a polydimethylsiloxane (PDMS) device, and Manz's research group demonstrated sub-second separation of two proteins in a free-flow IEF bed [9]. In addition, coupling IEF with a different separation mechanism (e.g., free-solution electrophoresis) in an orthogonal channel has been carried out for 2-D separations [10][11][12]. Efforts have also been reported that integrate IEF with multiple 2-D channels; these devices have a potential to perform better separation than conventional 2-D slab gel electrophoresis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the application of a high voltage is effective to obtain high-speed separation with high efficiencies in MCIEF. 35,36 To make sure, we checked the effect of Joule heating on the efficiency. In Eq.…”
Section: Mcief On Short Channel Chipmentioning
confidence: 99%